HUBUNGAN MOTIVASI BELAJAR DENGAN KETERAMPILAN MENULIS NARASI PADA SISWA KELAS V SD NEGERI 26 SINGKAWANG - Azira; Guna Utama, Erdi; Kamaruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine whether there is a significant relationship between learning motivation and the narrative writing skills of class V students at SDN 26 Singkawang. The method used in this research is a quantitative method with an associative research design. This research used a sample of all VB class students at SDN 26 Singkawang, totaling 22 students. Data collection techniques in this research are test and non-test techniques. The research instruments are a narrative writing skills test and a learning motivation questionnaire sheet. Data were analyzed using the Pearson product moment correlation formula with a significance level of 5% (0.05). The results of this research show that: (1) students' learning motivation is classified as good with a percentage of 83.18%, (2) students' narrative writing skills are classified as good with a percentage of 77.27%, (3) there is a significant relationship between learning motivation and writing skills. narrative with a correlation coefficient of 0.8515 (classified as very high) of 73%. It can be concluded that if a student's learning motivation is good, the better the student's writing skills, or conversely, the less the student's learning motivation, the worse the student's writing skills will be. Keywords: elementary education, motivation to learn, narrative writing skills